1998
DOI: 10.2527/1998.762474x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, endocrine, immune, and performance measures for pigs exposed to acute stress.

Abstract: Weanling pigs (n = 132) were used to investigate the effects of three common stressors (and a control) and differing social status on behavior, immunity, plasma cortisol, blood chemical, and performance measures. Eleven blocks of 12 pigs each were evaluated. Each pen contained three pigs of dominant (DOM), intermediate (INT), or submissive (SUB) social status. Two weeks later, random pens of pigs experienced either a control treatment (CON) or they were stressed for 4 h by shipping (SHIP), heat-stressed (HEAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
116
6
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(139 citation statements)
references
References 17 publications
9
116
6
2
Order By: Relevance
“…Although many stressors have been reported to increase plasma cortisol concentrations in pigs (Becker et al, 1985;Parrott and Misson, 1989), conflicting results have been reported by other researchers. For example, lower cortisol levels were detected in heat-stressed pigs compared with coldstressed and transportation-stressed pigs, with statistically similar values for cortisol compared with control pigs (Hicks et al, 1998, Sutherland et al, 2006. Furthermore, heat stress did not increase plasma cortisol in cows with the exception of a slight elevation on the first day of heat stress (Farooq et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many stressors have been reported to increase plasma cortisol concentrations in pigs (Becker et al, 1985;Parrott and Misson, 1989), conflicting results have been reported by other researchers. For example, lower cortisol levels were detected in heat-stressed pigs compared with coldstressed and transportation-stressed pigs, with statistically similar values for cortisol compared with control pigs (Hicks et al, 1998, Sutherland et al, 2006. Furthermore, heat stress did not increase plasma cortisol in cows with the exception of a slight elevation on the first day of heat stress (Farooq et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Stressors activate the hypothalamic-pituitary-adrenal axis, resulting in elevated corticotrophin-releasing hormone, which induces the release of ACTH and other peptides. Elevated ACTH stimulates the release of glucocorticoids from the adrenal cortex into the blood of stressed farm animals (Hicks et al, 1998). Although many stressors have been reported to increase plasma cortisol concentrations in pigs (Becker et al, 1985;Parrott and Misson, 1989), conflicting results have been reported by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…These changed biochemical indices in the offspring may indicate body condition differences, which may possibly lead to differences in growth in later life. In addition to physiological changes, animal behaviour also demonstrated responses to environment stressors (Hicks et al, 1998). Sows housed in groups demonstrated significantly higher drinking frequency than those in the stalls.…”
Section: Discussionmentioning
confidence: 99%
“…Tri-Solfen was also shown to be effective in reducing the post-procedural pain caused by surgical castration and tail docking (Paull et al, 2009;Lomax et al, 2010) and museling (Lomax et al, 2008) in lambs. Changes in leukocyte numbers and percentages can occur in response to acute stress in pigs (Hicks et al, 1998;Niekamp et al, 2007;Sutherland et al, 2009). This phenomenon is known as leukocyte trafficking and is thought to reflect the redistribution of leukocytes to lymph nodes, bone marrow and skin (Dhabhar, 2002).…”
Section: Discussionmentioning
confidence: 99%